The environmental impact of cultural change: Palynological and quantitative land cover reconstructions for the last two millennia in northern Poland. (10th July 2019) - Brown, Alex; Poska, Anneli; Pluskowski, Aleks
Abstract: This paper presents the first quantitative past land cover reconstructions for northern Poland using the Landscape Reconstruction Algorithm (LRA), interpreted alongside traditional percentage pollen data and historical sources. These data are used to evaluate the impact of cultural change on past vegetation and land-use in northern Poland during the last 2000 years. Vegetation change and land-use are apparent corresponding to the late Roman Iron Age (1st to 3rd centuries), Migration Period (4th–7th centuries), early Medieval (8th to early-13th centuries) and late medieval (early-13th to mid-15th centuries). The Roman Iron Age is characterised by significant land cover estimates for meadowland, likely part of a broad spectrum agricultural strategy. Widespread depopulation and woodland regrowth characterise the Migration Period, followed by the progressive clearance of woodland from the 7th/8th centuries corresponding to Slavic colonisation. Polish control of the region from the mid-10th century is accompanied by intensification in agricultural land-use. However, archaeological evidence for increasing settlement instability during the 11th/12th centuries is not obviously apparent in the palynological data. This likely reflects the sporadic nature and uneven impact of conflict, but also the difficulty in resolving short-term events in the palynological record. Significant woodland clearance occurred prior to the crusades, with the consequence that there is no clearly identifiable horizon of significant landscape change associated with the arrival of the Teutonic Order. However, large tracts of woodland survived in sparsely populated frontier zones and in areas with poor agricultural soils, managed as part of an extensive provisioning network covering the Teutonic Order's state.